2002
DOI: 10.1111/j.1479-8301.2002.tb00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset Psychosis with Agenesis of the Corpus Callosum

Abstract: Abstract:A 57-year-old woman showing her first psychiatric episode was admitted and MRI revealed agenesis of the corpus callosum with a lipoma. Except for the fact that her elder sister had been diagnosed with schizophrenia at the age of 24, she had no special anamnesis or problems in her life history. At the age of 57, troublesome behavior based on auditory hallucinations and delusions of persecution were noted which made it necessary for her to be taken to a hospital. There were no clinical signs of dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several studies looked into brain function and its association with late onset psychosis using EEG, ERP, positron emission tomography (PET) and single-photon emission computed tomography (SPECT). LOS subjects show a generalized slowing or a diffuse sharp and slow wave complex in their EEG [92][93][94][95], which points to changes in brain metabolism. These could only partially be explained by neuroleptic drug use.…”
Section: Connectivity and Functionality Of Different Brain Areasmentioning
confidence: 99%
“…Several studies looked into brain function and its association with late onset psychosis using EEG, ERP, positron emission tomography (PET) and single-photon emission computed tomography (SPECT). LOS subjects show a generalized slowing or a diffuse sharp and slow wave complex in their EEG [92][93][94][95], which points to changes in brain metabolism. These could only partially be explained by neuroleptic drug use.…”
Section: Connectivity and Functionality Of Different Brain Areasmentioning
confidence: 99%
“…Volumetric decrease of the corpus callosum among schizophrenic patients is regarded as one of the reasons for cognitive dysfunction in the transfer of information between the two cerebral hemispheres. Schizophrenic patients with partial or complete agenesis of the corpus callosum, which is associated with neurodevelopmental abnormality, have been occasionally reported [7], as has delusional disorder with complete agenesis of the CC [14]. One review has suggested that abnormalities in the limbic structure developed along with corpus callosum agenesis may be linked to psychiatric disorder [15].…”
Section: Discussionmentioning
confidence: 99%
“…A number of magnetic resonance imaging (MRI) studies on the brains of patients with schizophrenia showed cortical and subcortical abnormalities, including in the corpus callosum. Reports of schizophrenic patients with partial or complete agenesis of the corpus callosum, which is associated with neurodevelopmental abnormalities, have occasionally been cited [7,8].…”
Section: Introductionmentioning
confidence: 99%